(untitled) (Studia Prawnicze / The Legal Studies, 2023)
This academic contribution analyses the recent migration of a constitutional idea as a legal transplant in Central and Eastern Europe: the implementation of qualified law in several countries during their democratic transition. A cursory glance at the regional dimension of this constitutional instrument provides new insight into the role of qualified legislation during political transitions and leads to valuable experience regarding the migration of constitutional ideas in Central and Eastern Europe. It is demonstrated how the external, mainly Western European examples influenced the constitutional development of this region, and how the new democratic frameworks inspired each other within Central and Eastern Europe. Celem niniejszego opracowania naukowego jest analiza migracji idei konstytucyjnej w ostatnich dekadach w Europie Środkowej i Wschodniej traktowanej jako swoisty przeszczep prawny. Szczególną uwagę zwrócono na sposób wdrożenia prawa kwalifikowanego w wybranych państwach w okresie transformacji ustrojowej. Pobieżny ogląd regionalnego wymiaru tego instrumentu konstytucyjnego pozwala na pogłębienie wiedzy dotyczącej roli ustawodawstwa kwalifikowanego podczas przemian ustrojowych, co przekłada się na cenne doświadczenie w zakresie migracji idei konstytucyjnych w Europie Środkowo-Wschodniej. W artykule przedstawiono również wpływ zewnętrznych, głównie zachodnioeuropejskich wzorców na rozwój konstytucyjny objętych analizą państw oraz wzajemne oddziaływanie nowych ram demokratycznych w Europie Środkowo-Wschodniej.